Cochlear Dysfunction is not Common in Human Meningioma of the Internal Auditory Canal. Issue 10 (December 2017) - Landegger, Lukas D.; Lee, Jong D.; Linthicum, Fred H.; Stankovic, Konstantina M.
Abstract : Hypothesis: Cochlear dysfunction is not common in human meningioma of the internal auditory canal. Background: Meningiomas arising from the cerebellopontine angle and internal auditory canal typically cause hearing loss. Cochlear dysfunction is known to contribute to sensorineural hearing loss induced by vestibular schwannoma, the most common tumor of the internal auditory canal. Detailed cochlear histopathology in meningioma has not been reported. Methods: Retrospective analysis of cochlear histopathology in five unoperated and five operated meningiomas of the internal auditory canal identified after screening human temporal bone collections from three academic medical centers. Results: While some dysfunction of all analyzed cochlear cell types was identified, a predominant or exclusive loss of hair cells was not observed in any meningioma. Only 14.3% of temporal bones showed significantly more hair cell damage on the side of the tumor when compared with the contralateral ear; cochlear neuronal damage was more prevalent in meningiomas. The incidence of hydrops, perilymphatic precipitate, or endolymphatic precipitate was low. Conclusions: Substantial cochlear damage in human meningioma of the internal auditory canal is not common. This may explain the anecdotal hearing improvement observed after surgical resection of meningioma. Our findings underline the importance of developing therapeutic strategies to prevent cochlear neuronal degeneration due to tumors of the internal auditory canal. Abstract : Supplemental Digital Content is available in the text